AL-QUR'AN DAN MATERIAL GENETIK DALAM SEL KELAMIN PRIA PENENTU JENIS KELAMIN BAYI - Muchtaromah, Bayyinatul (ULUL ALBAB Jurnal Studi Islam, 2007)
In many verses of al-Qur'an, men are called to pay their attention to understand how they were created. Human creation and incredible aspects followed were strongly mentioned in many verses in detail until it's impossible for anyone who lived in the seventh century to recognize it. One of them was the information saying that the determinant of baby gender is the spermatozoa coming from men sperm. Allah said in his verse: "and that He (Allah) creates in pairs, male and female. From Nutfah (drops of semen male and female discharge) when it is emitted" (translation of al-Qur'an 53 verse 45-46). Branches of knowledge which have developed, such as Genetics and Molecular Biology, have proved scientifically the information accuracy which has been given by al-Qur'an. Nowadays it has been well-known that sex determination is determined by sperm of man and in fact women play no roles in this determination. If the ovum fuses with sperm which carries Y chromosome than the baby will be born as a male. Conversely, if the sperm carries X chromosome than the baby will be a female. In the other word, the sex of the baby is determined by the kind of man's sperm chromosome which fuses with women's ovum.